Implementation of the Free Nutritious Meal Program in Schools: A Systematic Literature Review of Success and Failure Factors - Nagaring, Sulaiman Putra; Lahay, Sitty Fadhilla Fitrianty; Nuryana, Riska; Martin, Novia; Siregar, Ryskina Fatimah (Universitas Negeri Gorontalo, 2026)
Background: Child nutrition problems in Indonesia remain a critical issue affecting health, education, and human resource quality. The government introduced the Makan Bergizi Gratis (MBG) Program to reduce stunting, improve learning concentration, and support socio-economic welfare. Nevertheless, its implementation faces challenges that may limit the achievement of long-term objectives.Content: This study applied a Systematic Literature Review (SLR) using articles published between 2020 and 2025 retrieved from Google Scholar. Inclusion criteria covered Indonesian and English publications addressing the implementation, effectiveness, or policy analysis of the MBG Program. From 396 identified articles, nine met the selection criteria. The findings indicate that the MBG Program positively impacts nutritional status, stunting reduction, student concentration and motivation, and local economic empowerment. Success is supported by strong leadership, local government involvement, transparent governance, multi-stakeholder collaboration, and policy adaptation. In contrast, major constraints include limited funding, fiscal sustainability issues, uneven logistics, weak regulations, low community participation, and unstable socio-political conditions.Conclusion: The MBG Program has strong potential as a long-term investment in achieving the Golden Generation 2045. Its success depends on stable financing, effective implementation, transparent governance, and sustained political commitment. Keywords: Free nutritious meal program, health policy, systematic literature review